HUMAN-COMPUTER INTERACTION: AI-DRIVEN GESTURE RECOGNITION - (:unkn) unknown (My University, 2024)
The integration of artificial intelligence (AI) in human-computer interaction (HCI) has significantly transformed how users engage with technology, particularly through gesture recognition. This paper explores the advancements in AI-driven gesture recognition systems, emphasizing their potential to enhance user experience across various applications, from gaming and virtual reality to accessibility tools and smart environments. We analyze the underlying algorithms and machine learning techniques that facilitate real-time gesture detection and interpretation, highlighting the importance of accuracy and responsiveness in user interactions. Additionally, the paper discusses the challenges faced in developing robust gesture recognition systems, including variability in user behavior, environmental factors, and the need for extensive training data. By examining case studies and recent innovations in the field, we illustrate the growing impact of AI-driven gesture recognition on user interfaces and the future of interactive technology. Ultimately, this research aims to provide insights into the transformative role of gesture-based interactions in creating more intuitive, immersive, and inclusive digital experiences.